2017
DOI: 10.1371/journal.pone.0175929
|View full text |Cite
|
Sign up to set email alerts
|

Modulation the alternative splicing of GLA (IVS4+919G>A) in Fabry disease

Abstract: While a base substitution in intron 4 of GLA (IVS4+919G>A) that causes aberrant alternative splicing resulting in Fabry disease has been reported, its molecular mechanism remains unclear. Here we reported that upon IVS4+919G>A transversion, H3K36me3 was enriched across the alternatively spliced region. PSIP1, an adapter of H3K36me3, together with Hsp70 and NONO were recruited and formed a complex with SF2/ASF and SRp20, which further promoted GLA splicing. Amiloride, a splicing regulator in cancer cells, could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Specific histone marks can affect the splicing outcome by recruiting splicing factors to the site of transcription (Podlaha et al ., ; Zhou et al ., ). Moreover, we have demonstrated that amiloride reversed aberrant histone modification patterns, resulting in the disruption of the association of splicing complex with the transcripts (Chang et al ., ). To investigate whether histone‐tail PTMs are involved in the BS008‐regulated splicing, we analyzed the effects of BS008 on histone‐tail PTMs in Huh‐7 cells.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Specific histone marks can affect the splicing outcome by recruiting splicing factors to the site of transcription (Podlaha et al ., ; Zhou et al ., ). Moreover, we have demonstrated that amiloride reversed aberrant histone modification patterns, resulting in the disruption of the association of splicing complex with the transcripts (Chang et al ., ). To investigate whether histone‐tail PTMs are involved in the BS008‐regulated splicing, we analyzed the effects of BS008 on histone‐tail PTMs in Huh‐7 cells.…”
Section: Resultsmentioning
confidence: 97%
“…Taken together, these results suggested that PP1 phosphatase rather than AKT kinase was associated with the dephosphorylation of SRSF3, which in turn played a role in the BS008‐modified AS process. In this regard, BS008 appears similar to amiloride, which regulates the AS through a PP1‐mediated splicing mechanism (Chang et al ., ,, ).…”
Section: Resultsmentioning
confidence: 99%
“…NONO also additionally interacts with the C‐terminal of RNA pol IIa and IIo . In some conditions, NONO can also interact with 3′ end of mRNA splicing such as TNF‐a, the exonuclease XRN2, the snRNP‐free U1A and GLA (α‐galactosidase A) …”
Section: Nono and Gene Regulationmentioning
confidence: 99%
“…Through medical and technological development, enzyme replacement therapy (ERT) and chaperone therapy are now available [ [5] , [6] , [7] ], and neonatal and high-risk screening is performed for early diagnosis and early treatment of Fabry patients [ [8] , [9] , [10] , [11] , [12] , [13] ]. Accordingly, an effort to elucidate the characteristics of Fabry patients in various countries and areas has been made [ [11] , [12] , [13] , [14] , [15] , [16] ]. For example, in Japan, many case reports and results of small cohort studies have been published [ [17] , [18] , [19] , [20] ].…”
Section: Introductionmentioning
confidence: 99%